Dynamic Magnetic Resonance Imaging of the Pharynx during Deglutition. (March 2013) - Amin, Milan R.; Achlatis, Stratos; Lazarus, Cathy L.; Branski, Ryan C.; Storey, Pippa; Praminik, Bidyut; Fang, Yixin; Sodickson, Daniel K.
Objectives: We utilized dynamic magnetic resonance imaging to visualize the pharynx and upper esophageal segment in normal, healthy subjects. Methods: A 3-T scanner with a 4-channel head coil and a dual-channel neck coil was used to obtain high-speed magnetic resonance images of subjects who were swallowing liquids and pudding. Ninety sequential images were acquired with a temporal resolution of 113 ms. Imaging was performed in axial planes at the levels of the oropharynx and the pharyngoesophageal segment. The images were then analyzed for variables related to alterations in the area of the pharynx and pharyngoesophageal segment during swallowing, as well as temporal measures related to these structures. Results: All subjects tolerated the study protocol without complaint. Changes in the area of the pharyngeal wall lumen and temporal measurements were consistent within and between subjects. The inter-rater and intra-rater reliabilities for the measurement tool were excellent. Conclusions: Dynamic magnetic resonance imaging of the swallow sequence is both feasible and reliable and may eventually complement currently used diagnostic methods, as it adds substantive information.